1977
DOI: 10.1017/s0007123400001022
|View full text |Cite
|
Sign up to set email alerts
|

From Life Space to Polling Place: The Relevance of Personal Concerns for Voting Behavior

Abstract: To live is to have problems. However the country as a whole fares, the individual has bills to pay, work to do, children to worry about – to mention only a few of the commonplace problems that people face in their daily lives. Commonplace or not, these are problems that people must wrestle with. They are immediate, inescapable, and serious, far more so for most than the ‘large’ issues facing the country. Students of voting have long suspected that such problems may influence political choices, but key question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(98 citation statements)
references
References 3 publications
4
94
0
Order By: Relevance
“…However, our interpretation of this phenomenon differs somewhat from theirs. The factor loadings of the personal economic concerns coincides with the argument that people generally do not connect their own situation with politics because they are self-rather than system-blaming (Brody & Sniderman, 1977;Kinder & Kiewiet, 1979). The difference in interpretation comes with regard to the items presumed to measure collective orientation.…”
Section: Assessing the Validity Of Available Measuressupporting
confidence: 64%
“…However, our interpretation of this phenomenon differs somewhat from theirs. The factor loadings of the personal economic concerns coincides with the argument that people generally do not connect their own situation with politics because they are self-rather than system-blaming (Brody & Sniderman, 1977;Kinder & Kiewiet, 1979). The difference in interpretation comes with regard to the items presumed to measure collective orientation.…”
Section: Assessing the Validity Of Available Measuressupporting
confidence: 64%
“…al 1960;Franklin, Lyons, and March 2004;Plutzer 2002). More recently, several papers document the positive correlation between past and current decisions in the most central political behavior: voter turnout (Brody and Sniderman 1977;Goldstein and Ridout 2002;Verba and Nie 1972). As a result, Plutzer (2002, p. 42) argues that "virtually all major works on turnout have concluded that voting behavior is, in part, a gradually acquired…”
Section: Literaturementioning
confidence: 99%
“…For example, if income has an impact on turnout and individual incomes usually do not change, then what seems like habitual turnout might be persistence in income levels over time. To that end, several studies have controlled for both known and unknown factors that might influence turnout using standard analysis of National Election Studies panel data (Brody and Sniderman 1977), instrumental variables analysis of the same data (Green and Shachar 2000), and evidence from a randomized field experiment (Gerber, Green, and Shachar 2003). These studies all find that past voting behavior is positively and strongly correlated with future voting behavior-people who voted 3 For example, in 1,000 simulations using BDT's base model assumptions, 98% of the individual propensities end up closer to .5 than to 0 or 1. in the previous election turn out at a rate of about 50 percentage points higher than those who do not.…”
Section: E P P a P A P I T I T I T I T I T I T I T I Tmentioning
confidence: 99%